Meanings on public and private spatiality in popular sectors of the Gran Buenos Aires (PAMPA, 2025)
The article analyses social representations on the neighbourhood space elaborated by inhabitants of a popular neighbourhood of the Gran Buenos Aires, situated in Quilmes Town and characterized by a strong social and environmental vulnerabilities. However, meanings on the space of proximity do not recreate linealy those infrastructural deficits. On the contrary, they are framed by a complex symbolic structure, which solves tensions between public and private-household spacialities, uses and state’s acknowledgment, as well as city’s images, formalization horizons and informal conditions. Analysis is based on a series of semi-structured interviews, developed in 2021.
Keywords: Public spaces; Neighbourhood space; Household policies; Social representations